Gambaran Health Belief pada Perokok Pelajar SMP - Raisa Qurratu ‘Ain Fasa; Dinda Putri Pratama; Raihani Akmalia Lubis; Resti Juliana Putri; Wahyu Ramadhani (Departemen Psikologi, Universitas Negeri Padang, 2024)
Smoking behavior among adolescents is a serious health issue. Smoking has been shown to be detrimental to health. The more often individuals smoke cigarettes, the more at risk they are of developing chronic diseases in the future. Smoking behavior is personal where the decision to smoke is based on the individual's own wishes. Health belief theory can be applied to examine how individuals behave towards disease prevention measures and adherence to them. This study aims to determine how the description of health beliefs in junior high school student smokers. This study uses a descriptive quantitative approach that applies accidental sampling techniques and the number of respondents is 41 people. The technique used to analyze the data is descriptive statistics. The results showed that 85.4% of respondents had strong health beliefs. Basically, they believe in the benefits of quitting smoking, but still face obstacles that make it difficult to stop the habit of smoking behavior.